Implications for the Power of Attorney to Sell Deed Made by a Notary Due to Inaccuracy - Samosir, Tetti; Indah Harlina; Vicky (Inovasi Pratama Internasional. Ltd, 2025)
The role of a notary is crucial in facilitating legal certainty and protection for the community. In civil law, notaries hold a highly strategic position as their profession deals with fundamental and critical issues in every legal action, particularly within civil law. The public, both as subjects and objects of legal transactions, bear significant burdens regarding legal administration. Violations by notaries can be classified as breaches of professional ethics or breaches of the law, with consequences that may include civil liabilities (compensation), criminal penalties (imprisonment and fines), and administrative sanctions (dismissal from office). Every unlawful action causing harm to others must be accounted for by the perpetrator. In criminal law theory, offenses are categorized into intentional and negligent acts. Any action causing undue harm and violating the law constitutes an illegal act. This study analyzes the juridical implications of drafting a power of attorney for sale from normative and case-based perspectives. The research revealed that a notary's failure to conduct adequate checks on document legality for a Power of Attorney for Sale resulted in unlawful actions that harmed legitimate parties, leading to material losses.